Viral distribution of Newcastle disease virus genotype VII in different organs of broiler chickens - Khader, Manar A. A.; El-Kady, Magdy F.; Shaheed, Iman B. (Brazilian Journal of Veterinary Pathology, 2020)
The poultry industry in Egypt is still threatened by Newcastle disease despite intensive vaccination programs. Both vaccinated and unvaccinated poultry flocks have experienced Newcastle disease virus (NDV) genotype VII outbreaks within the last few years. This study was performed to investigate the pathogenesis of NDV genotype VII in different organs of broiler chickens. Fifty, 1-day-old chicks were divided into 2 equal groups with 25 animals in each group. Group 1 served as the non-infected (negative control) group, while group 2 was infected by intranasal inoculation of 0.1 ml containing 106 EID50 of NDV genotype VII. Three chicks were sacrificed from each group at 2, 5, and 10 days post-infection (dpi). Tissue sections from the nasal conchae, larynx, trachea, lungs, heart, kidneys, and brain were collected for histopathology and immunohistochemistry. Quantitative RT-PCR (qRT-PCR) was also performed on the tracheal samples. The infected group showed severe respiratory signs and had greenish-colored diarrhea. Mortalities were 6, 4, 6, and 2 chicks at 5, 6, 7, and 9 dpi, respectively. Grossly, congestion of the mucosa of the trachea and larynx was recorded at 5 dpi. Histopathological examination of different organs revealed tracheitis, pneumonia, laryngitis, nephritis, brain perivascular cuffing, and neuronal degeneration. NDV antigen was detected by IHC in all examined organs except the brain. Strong viral antigen expression by IHC was observed at 5 and 7 dpi in most of the studied organs. Viral antigen expression was also detected in the endothelial cells of blood vessels, cilia, surface epithelium, and goblet cells of the nasal conchae, larynx, and trachea in addition to the cytoplasm of cardiomyocytes and in the epithelium lining the renal tubules.